Image quality evaluation for a clinical organ-targeted PET camera - Baldassi, Brandon; Poladyan, Harutyun; Shahi, Anirudh; Maa-Hacquoil, Henry; Rapley, Madeline; Komarov, Borys; Stiles, Justin; Freitas, Vivianne; Waterston, Michael; Aseyev, Olexiy; Reznik, Alla; Bubon, Oleksandr (Frontiers in Oncology, 2024)
A newly developed clinical organ-targeted Positron Emission Tomography (PET) system (also known as Radialis PET) is tested with a set of standardized and custom tests previously used to evaluate the performance of Positron Emission Mammography (PEM) systems. Imaging characteristics impacting standardized uptake value (SUV) and detectability of small lesions, namely spatial resolution, linearity, uniformity, and recovery coefficients, are evaluated.In-plane spatial resolution was measured as 2.3 mm ±0.1 mm, spatial accuracy was 0.1 mm, and uniformity measured with flood field and NEMA NU-4 phantom was 11.7% and 8.3% respectively. Selected clinical images are provided as reference to the imaging capabilities under different clinical conditions such as reduced activity of 2-[fluorine-18]-fluoro-2-deoxy-D-glucose ( 18 F-FDG) and time-delayed acquisitions. SUV measurements were performed for selected clinical acquisitions to demonstrate a capability for quantitative image assessment of different types of cancer including for invasive lobular carcinoma with comparatively low metabolic activity.Quantitative imaging performance assessment with phantoms demonstrates improved contrast recovery and spill-over ratio for this PET technology when compared to other commercial organdedicated PET systems with similar spatial resolution. Recovery coefficients were measured to be 0.21 for the 1 mm hot rod and up to 0.89 for the 5 mm hot rod of NEMA NU-4 Image Quality phantom. Demonstrated ability to accurately reconstruct activity in tumors as small as 5 mm